Risk factors of postoperative prolonged ileus after colorectal cancer surgery - E. A. Khomyakov; E. G. Rybakov; I. V. Zarodnyuk; Yu. A. Shelygin; D. Yu. Pikunov (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The authors identified independent risk factors of postoperative prolonged ileus after colorectal cancer surgery. MATERIAL AND METHODS. Multivariate logit regression analysis was made in order to reveal independent risk factors of prolonged ileus. RESULTS. The frequency of prolonged ileus cases consisted of 13 %. The authors detected three independent risk factors such as body mass index higher than 25 kg/m² (p=0,033), taking of opioid analgetics (p=0,022) and left colon flexure mobilization (p=0,047) in multivariate statistical analysis. CONCLUSIONS. Postoperative prolonged ileus was the frequent complication in colorectal cancer surgery. There is a possibility to identify the group of patients who exposed to risk of occurrence of prolonged postoperative ileus due to application of revealed risk factors.